WASTE PROCESSING TRAINING AS AN ALTERNATIVE MATERIAL FOR CANDLES - Nuri Suryani; Nana Krisdianti; Riski Pradana; Muhammad Taupik; Singgih Subiyantoro (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
In their life, the people of Siwal Village cannot be separated from the use of oil. Moreover, the majority of Siwal Village residents work as food or fried food sellers on the roadside. Repeated use of cooking oil can have harmful effects on health. In addition, used cooking oil that can no longer be used is usually dumped in careless places and causes environmental pollution. Another problem in Siwal Village is the lack of skills of children due to the influence of gadgets. With these things in mind, training on how to process used cooking oil into an alternative material for making used used wax is one of the right solutions. Activities consist of a location survey, implementation, results and discussion. Implementation includes; 1) preparation 2) counseling 3) training 4) mentoring 5) evaluation 6) advanced stage training. All activities carried out online are able to improve children's skills and reduce environmental pollution due to used waste. Keywords: oil, used cooking, wax